Expanding social protection coverage with humanitarian aid: Lessons on targeting and transfer values from Ethiopia - Sabates-Wheeler, Rachel; Hirvonen, Kalle; Lind, Jeremy; Hoddinott, John F. (Informa UK Limited, 2022)
While social protection programmes have multiplied over the last two decades across sub-Saharan Africa, these coexist alongside humanitarian assistance in many places, calling for better integration of assistance delivered through the two channels. Progress on this front is hampered by limited evidence of whether and how these historically siloed sectors can work together. Using quantitative and qualitative data from districts covered by Ethiopia’s Productive Safety Net Programme (PSNP) and where humanitarian food assistance (HFA) was delivered, we assess differences in targeting and transfer values. We find that the PSNP and HFA were targeted to households with different characteristics. PSNP transfers did, on average, reach those households that were chronically food insecure. HFA, while delivered through the PSNP systems, was targeted to households that were acutely vulnerable. These are promising findings as they suggest that social protection systems are able to effectively deliver a continuum of support in response to different types of vulnerability and risk. On transfer values, we find that the value of PSNP transfers is greater than those for HFA. One reason for this may be due to the social pressure on local officials to distribute support more widely across a drought-affected population when faced with acute needs.